Randomised clinical trial: symptoms of the irritable bowel syndrome are improved by a psycho‐education group intervention. Issue 3 (3rd December 2012) - Labus, J.; Gupta, A.; Gill, H. K.; Posserud, I.; Mayer, M.; Raeen, H.; Bolus, R.; Simren, M.; Naliboff, B. D.; Mayer, E. A.
Summary Background Evidence supports the effectiveness of cognitive behavioural approaches in improving the symptoms of the irritable bowel syndrome (IBS). Duration, cost and resistance of many patients towards a psychological therapy have limited their acceptance. Aim To evaluate the effectiveness of a psycho‐educational intervention on IBS symptoms. Methods Sixty‐nine IBS patients (72% female) were randomised to an intervention or a wait‐list control group. The IBS class consisted of education on a biological mind body disease model emphasising self‐efficacy and practical relaxation techniques. Results Patients in the intervention showed significant improvement on GI symptom severity, visceral sensitivity, depression and QoL postintervention and most of these gains were maintained at 3‐month follow‐up (Hedge's g = −0.46–0.77). Moderated mediation analyses indicated change in anxiety, visceral sensitivity, QoL and catastrophising due to the intervention had moderate mediation effects (Hedge's g = −0.38 to −0.60) on improvements in GI symptom severity for patients entering the trial with low to average QoL. Also, change in GI symptom severity due to the intervention had moderate mediation effects on improvements in QoL especially in patients with low to average levels of QoL at baseline. Moderated mediation analyses indicated mediation was less effective for patients entering the intervention with high QoL. Conclusions A brief psycho‐educational group intervention is efficacious in changing cognitions and fears about the symptoms of the irritable bowel syndrome, and these changes are associated with clinically meaningful improvement in symptoms and quality of life. The intervention seems particularly tailored to patients with low to moderate quality of life baseline levels.